AESTHETIC CONSIDERATIONS ON PONTIC FIXED PROSTHESIS VS. SINGLE RESTAURATIONS - Mădălina Mihali; Gabriela Roșu; Vasile Huțanu; Petruța Siminiuc; Eduard Adam; Radu Ioan Alexandru; Kamel Earar (Romanian Dental Association for Education, 2023)
Aim of the study: The social and psychological role of a pleasant smile is well known. In addition to the aesthetic aspect, the functional role of a complete dento-maxillary system, with a normal function that ensures mastication and phonation, are of great importance [1]. The present article regards all the criteria that have to be met in order to achieve high aesthetic results weather is done with fixed prosthesis or individual restorations. Materials and methods: Literature data research was performed in order to analyse the comprehensive criteria needed for prosthodontics treatment in the aesthetic area. Two clinical cases are presented as result of following predictable protocol for treatment in the aesthetic area. Results and Conclusions: Obtained results clearly show the importance of prosthodontics by establishing integrity of dental arches, restoring functional guides, aesthetics and phonatory function. For young patients, who require fixed prosthetic restorations, it is fundamental to consider the translucency of the incisal margin especially when not all the frontal group is restored. Respecting translucency along with all the other key elements of prosthodontic restoration ensure a special aesthetic integration in the context of the natural arch.